2012
DOI: 10.1103/physrevd.86.115002
|View full text |Cite
|
Sign up to set email alerts
|

Charged Higgs boson detection in theτνdecay mode at future linear colliders

Abstract: The charged Higgs boson phenomenology and discovery potential at future linear colliders through the production process e À e þ ! H þ H À ! þ " is studied. Both charged Higgs bosons are considered to decay to , and the hadronic decay of leptons is analyzed, taking into account spin and kinematics effects using a proper simulation of the -lepton decay. It is shown that within the minimal supersymmetric standard model framework, with tan ¼ 10, a wide range of charged Higgs masses would have a detectable signal b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…Double Higgs or pair production of charged Higgs bosons at linear colliders, has been extensively investigated in the literature mainly in MSSM in the context of e + e − and µ + µ − colliders, [20][21][22][23].…”
Section: Charged Higgs Pair Productionmentioning
confidence: 99%
“…Double Higgs or pair production of charged Higgs bosons at linear colliders, has been extensively investigated in the literature mainly in MSSM in the context of e + e − and µ + µ − colliders, [20][21][22][23].…”
Section: Charged Higgs Pair Productionmentioning
confidence: 99%
“…Theoretical studies of the possibility of observation of a charged Higgs at various colliders are numerous [87][88][89][90][91] including analysis in the tb channel [92] which showed that a mass range of about 300 to 600 GeV for tan β = 30 may be observable with about 1000 fb −1 of integrated luminosity. The τ ν channel has also been studied [93,94]. Before we discuss the result of our analysis we describe the different codes utilized in simulation of the signals and backgrounds.…”
Section: Discovery Potential In the H ± → τ ν Channelmentioning
confidence: 99%